Negative Air Pressure on Wet Cupping in Decreasing Blood Pressures in Hypertensive Patients - Darmawan, Budi; Fatmasari, Diyah; Pujiastuti, Rr. Sri Endang (Department of Nursing, Faculty of Medicine, Diponegoro University, 2017)
Background: Wet cupping, furthermore mentioned cupping, decreases blood pressures through the level of negative air pressures added by hydrostatics filtration pressure to reinforce the power of fluids filtration in capillaries. However, an appropriate negative air pressure to decrease blood pressure remains an uncertainty.Purpose: This study aimed to analyze negative air pressure differences on cupping in decreasing blood pressures in hypertensive patients.Methods: This is a quasi-experimental design conducted in three Community Health Centers in Langsa City, Aceh, Indonesia. The samples were 36 hypertensive males with age from 45 to 55, who were randomly stratified into two groups with cupping pressures 400 mbar (n=18) as the control group; and 540 mbar (n=18) as the intervention group. The cupping session was performed to each group on T1 (alkahil) point and in the middle line of both shoulders blade points. The systolic blood pressure (SBP) and diastolic blood pressures (DBP) were measured by validated automatic sphygmomanometer. The follow-up periods were one week and two weeks. The data were then analyzed by repeated measures ANOVA.Results: Cupping pressure of 400 mbar decreased the mean of SBP and DPB with a p-value of 0.450 and 0.026, respectively after two weeks of intervention. Meanwhile, cupping pressure of 540 mbar decreased the mean of SBP and DBP with a p-value of 0.006 and 0.057, respectively. Tests of within-subjects resulted in the p-value of 0.250 (SBP) and 0.176 (DBP) after two weeks of intervention. There were no significant differences in SBP and DBP between the intervention group and the control group.Conclusion: The cupping pressure between 400 mbar and 540 mbar could reduce blood pressure; however, the cupping pressure of 540 mbar yielded greater effect in decreasing blood pressure than the 400 mbar. Negative air vacuum pressure loads on cupping to decrease blood pressure should be considered between 400 to 540 mbar, and further studies are needed.